2021
DOI: 10.1136/bmj.n1506
|View full text |Cite
|
Sign up to set email alerts
|

Use of cast immobilisation versus removable brace in adults with an ankle fracture: multicentre randomised controlled trial

Abstract: Objectives To assess function, quality of life, resource use, and complications in adults treated with plaster cast immobilisation versus a removable brace for ankle fracture. Design Multicentre randomised controlled trial. Setting 20 trauma units in the UK National Health Service. Participants 669 adults aged 18 years and older with an acute ankle fracture suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 20 publications
5
35
0
Order By: Relevance
“…Further details on eligibility can be found in the protocol 7 and the main clinical results. 6 The AIR trial was approved by the UK National Research Ethics Committee (17/WM/0239). trial recruitment and demographics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details on eligibility can be found in the protocol 7 and the main clinical results. 6 The AIR trial was approved by the UK National Research Ethics Committee (17/WM/0239). trial recruitment and demographics.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on trial recruitment and demographic information of participants can be found in the clinical paper. 6 Resource use data. Data were recorded using case report forms at six, ten, 16, and 24 weeks, and 12 months postrandomization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ankle Injury Rehabilitation trial radiology manual was consulted with permission as part of the scoping review. 18,19 An e-Delphi exercise was undertaken to establish consensus on the FPA candidate items where no agreement exists. The consensus benchmark was set at ≥ 75% panel agreement, which is line with usual practice in the consensus setting literature.…”
Section: Introductionmentioning
confidence: 99%
“…The Ankle Injury Rehabilitation trial radiology manual was consulted with permission as part of the scoping review. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%